2021
DOI: 10.3389/fimmu.2021.663115
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory Monocyte Subset Promotes Metastasis Associated With Therapeutic Intervention for Primary Tumor

Abstract: Systemic and local inflammation associated with therapeutic intervention of primary tumor occasionally promotes metastatic recurrence in mouse and human. However, it remains unclear what types of immune cells are involved in this process. Here, we found that the tissue-repair-promoting Ym1+Ly6Chi monocyte subset expanded as a result of systemic and local inflammation induced by intravenous injection of lipopolysaccharide or resection of primary tumor and promoted lung metastasis originating from circulating tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…1b). Lung tumor burdens were also found to be lower in IAV-infected mice, as demonstrated by reduced B16-luc-specific gene transcripts of premelanosome (Pmel) 34 and luciferase in the lung (Extended Data Fig. 2a) and reduced luciferin tumor signals in the lung area (Fig.…”
Section: Acute Iav Infection Induces Long-lasting Pulmonary Antitumor...mentioning
confidence: 92%
See 1 more Smart Citation
“…1b). Lung tumor burdens were also found to be lower in IAV-infected mice, as demonstrated by reduced B16-luc-specific gene transcripts of premelanosome (Pmel) 34 and luciferase in the lung (Extended Data Fig. 2a) and reduced luciferin tumor signals in the lung area (Fig.…”
Section: Acute Iav Infection Induces Long-lasting Pulmonary Antitumor...mentioning
confidence: 92%
“…injection of B16-luc cells expressing green fluorescent protein (GFP) 27,35 . By quantifying gene transcripts of premelanosome (Pmel), dopachrome tautomerase (Dct) 34 and luciferase as well as the numbers of CD45 -GFP + B16 cells, we showed comparable early tumor burdens in the lungs between PBS-treated and IAV-infected mice (Extended Data Fig. 2c,d).…”
mentioning
confidence: 85%
“…While the literature is controversial about the importance of MCP1 in obesity-induced inflammation ( 47 , 48 ), using the chemokine and PA treatment, we identified that male monocytes specifically have a more robust trafficking response in vitro. Sex differences in migration could be attributed to monocytes being heterogenous in nature with respect to the various chemokine and cytokine receptors where some are involved in tissue damage, while others promote tissue repair ( 49 51 ). MCSF facilitates tissue repair by recruiting monocytes to inflammation sites through CCR2 receptor activation and induction of CCL2/MCP1 production ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…There were notable increases in the numbers of monocytes (Ly6C + and Ly6C – ) and neutrophils in the metastasis models. A recent study showed that the number of Ym1 + /Ly6C hi monocytes was increased in the peripheral blood of mice with early stages of lung metastasis, suggesting that the proportion of monocytes can be used as a biomarker of metastasis ( 22 ). Another study reported that injection of LLC1 cells to mice with Ifnar1 promoted the development of lung metastasis together with the accumulation of neutrophils in the lung, indicating the involvement of neutrophils in metastasis ( 23 ).…”
Section: Discussionmentioning
confidence: 99%